The Impact of Agile Management on the Performance of Yemeni Pharmaceutical Industry Companies in the Capital Municipality of Sana’a - Joail, Majid Mabkot Mabkot; Al-Meshreqi, Zainab Abdo F. O. (University of Science and Technology Journal for Management and Human Sciences, 2025)
This study aimed to identify the impact of agile management (5S, six sigma, work standard, continuous improvement, and cross-functional teams) on performance (financial, customers, internal operations, and education and growth) of Yemeni pharmaceutical industry companies in the Capital Municipality of Sana’a. A descriptive analytical approach was employed, and primary data were collected through a questionnaire distributed to 278 employees across companies following a stratified random sampling method; of which (270) questionnaires were valid for analysis using SPSS. The study revealed that there is an impact of agile management on performance across the companies. The results also showed that there are no statistically significant differences in the level of performance across the companies attributed to the organizational variables (company size and age). Based on these findings, the study recommends that pharmaceutical manufacturing companies in Sana’a should pay more attention to agile management due to its role in performance, and also focus on improving and developing employees to enable them to achieve higher levels of performance in the long term.
Keywords: agile management; performance; balanced scorecard approach; Yemeni pharmaceutical industry companies